Plus tree selection as an improved source for propagation of Eucalyptus camaldulensis - Qader, Nozad Ali; Ab Shukor, Nor Aini; Md. Tahir, Paridah; Abdul Kadir, Mihdzar (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Tree improvement is the implementation of genetic principles to boost the value and improve the genetic gain of tree crops. Tree selection is one of the most important processes of a tree improvement programme. Thus, this study was conducted to obtain improved materials for propagation of Eucalyptus camaldulensis through screening, selection and reselection of appropriate genotypes. Sixty plus trees of two aged groups (5 and 10 year-old) from two plantations i.e. Khabat (K) and Pirde (P), Iraq were screened for growth parameters (selected quantitative and qualitative traits for paper production). The respective plus trees were numbered 1 to 15 for different aged-groups and plantations. Then, sixteen trees were then reselected and identified as potential sources for propagation based on growth parameter, i.e. size, height, diameter, crown height, clear bole height, branching habit, straightness, number of knots, number of branches and state of health in addition to fibre morphology parameters, i.e. fibre length, fibre diameter, cell wall thickness, lumendiameter, flexibility and Runkle ratio. Upon screening and analyses based on the combination of growth and fibre morphology parameters, seven plus trees were re-identified as the sources of the improved materials for propagation. They are tree no. 5K-8, 10K-3, 10K-15, 5P-3, 5P-6, 10P-7 and 10P-12. The best source based from this cumulative assessment is tree no. 10P-12.